Embodying Bounded Rationality: From Embodied Bounded Rationality to Embodied Rationality - Petracca, Enrico (Frontiers in Psychology, 2021)
Views of embodied cognition vary in degree of radicalism. The goal of this paper is to explore how the range of moderate and radical views of embodied cognition can inform new approaches to rationality. In this exploration, Herbert Simon’s bounded rationality is taken for its complete disembodiedness as a reference base against which to measure the increasing embodied content of new approaches to rationality. We use the label ‘embodied bounded rationality’ to explore how moderate embodiment can reform Simon’s bounded rationality while, on the opposite side of the embodied spectrum, the label ‘embodied rationality’ is employed to explore how radical embodiment can more deeply transform the idea of what is rational. In between the two poles, the labels ‘body rationality’ and ‘extended rationality’ are introduced to explore how also intermediate embodiment can fruitfully inform the research on rationality.